SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Incorporating fire severity mapping into fuel accumulation curves - Christopher E. Gordon; Luke Collins; Meaghan Jenkins; Brett P. Murphy; Trung H. Nguyen; Owen F. Price; Liubov Volkova; Christopher J. Weston; Rachael H. Nolan (Science of The Total Environment, 2026)

Drought, topography, and forest management shape wildfire occurrence and severity in montane Australian landscapes - Jeremy Johnson; Luke T. Kelly; Luke Collins; Stephen Stewart; Craig R. Nitschke (Science of The Total Environment, 2025)

Anthozoan eDNA primer set characterizes Ctenophora and Medusozoa inhabiting mesophotic and deep waters off the Gulf Coast of the southern USA - Annemarie Wood; Luke McCartin; Santiago Herrera; Andrea M. Quattrini; Allen G. Collins (Frontiers in Marine Science, 2025)
While gelatinous zooplankton (GZ) constitute a vital component of the marine food web, understanding their biology and ecology has been hindered because traditional collection methods often destroy their fragile bodies. Environmental DNA (eDNA) sequencing is a non-invasive approach that can detect organisms that are difficult to sample, enabling the DNA of understudied taxa to be sequenced. Here, we present the first application of eDNA metabarcoding targeting Ctenophora and Medusozoa. We first assessed the applicability of an anthozoan eDNA primer set designed to a 28S barcode in anthozoans for amplifying this region in ctenophores and medusozoans, including the creation of a 28S reference library for Ctenophora. After determining that the primers complement these groups well, the primers were used to analyze eDNA samples from mesophotic and deep-sea sites off the Gulf Coast of the southern USA. We recovered sequences belonging to a diverse array of GZ taxa and used these data to distinguish GZ communities by site and ecosystem type, characterize community diversity, and facilitate a better understanding of how these mysterious organisms interact within their ecosystem. The versatility of this primer set presents an exciting opportunity to research taxa that have been historically difficult to study, while further contributing to our understanding of their ecological roles in the deep sea.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Demographic change and loss of big trees in resprouting eucalypt forests exposed to megadisturbance - Eli R. Bendall; Luke C. Collins; Kirsty V. Milner; Michael Bedward; Matthias M. Boer; Brendan Choat; Rachael V. Gallagher; Belinda E. Medlyn; Rachael H. Nolan (Global Ecology and Biogeography, 2024)
Aim Increased tree mortality linked to droughts and fires is occurring across temperate regions globally. Vegetation recovery has been widely reported; however, less is known about how disturbance may alter forests structurally and functionally across environmental gradients. We examined whether dry forests growing on low‐fertility soils were more resilient to coupled extreme drought and severe fire owing to lower tree mortality rates, higher resprouting success and persistence of juveniles relative to wetter forests on more fertile soils. Location Fire‐tolerant eucalypt forests of temperate southeastern Australia. Time period 2020–2023. Major taxa studied Eucalyptus , Corymbia , Angophora . Methods Demographic surveys of tree mortality and regeneration in all combinations of dry/wet forest, fertile/less fertile substrates exposed to extreme drought and fire were conducted. We used Bayesian regression modelling to compare tree mortality, diameter, response traits, population structure and occurrence of fire scars between substrates/forest types. Results Overall mortality (20%–33%) and topkill (34%–41%) were within historically reported ranges for various forests and soil types. However, we observed an atypical trend of increased mortality and topkill in the largest trees, particularly when they had structural damage from past fires. Trees in wet forests on more fertile soils had the highest levels of mortality. Numbers of persistent resprouting juveniles were highest in dry forests on low‐fertility soils. Dry forests growing on low‐fertility soils appear more resilient to compound disturbances due to lower rates of mortality and higher rates of juvenile persistence. Wet forests on more fertile soils may experience greater demographic change due to higher mortality of small and large trees. Main conclusions Mesic forests on relatively fertile soils were found to be at relatively high risk of demographic change from compound disturbances. Combined, fire and drought are likely to reduce the number of large trees in affected areas, with consequences for forest carbon cycling and storage.

Atmospheric dryness removes barriers to the development of large forest fires - Jane G. Cawson; Luke Collins; Sean A. Parks; Rachael H. Nolan; Trent D. Penman (Agricultural and Forest Meteorology, 2024)

Unburnt refugia support post-fire population recovery of a threatened arboreal marsupial, Leadbeater’s possum - Louise K. Durkin; Paul D. Moloney; Jemma K. Cripps; Jenny L. Nelson; Phoebe V. Macak; Michael P. Scroggie; Luke Collins; Luke D. Emerson; Jamie Molloy; Lindy F. Lumsden (Forest Ecology and Management, 2024)

Effects of a megafire vary with fire severity and forest type: The impact of Australia's ‘Black Summer’ fires on the superb lyrebird (Menura novaehollandiae), an iconic forest species - Alex C. Maisey; Luke Collins; Graeme Newell; Andrew F. Bennett (Biological Conservation, 2023)

The power of eDNA sampling to investigate the impact of Australian mega-fires on platypus occupancy - Emily F. McColl-Gausden; Josh Griffiths; Luke Collins; Andrew R. Weeks; Reid Tingley (Biological Conservation, 2023)

Warmer and drier conditions have increased the potential for large and severe fire seasons across south‐eastern Australia - Luke Collins; Hamish Clarke; Michael F. Clarke; Sarah C. McColl Gausden; Rachael H. Nolan; Trent Penman; Ross Bradstock (Global Ecology and Biogeography, 2022)
Aim The aims were: (1) to identify the environmental drivers of interannual variation in wildfire extent and severity; (2) to examine temporal trends in climatic potential for large and severe wildfires; and (3) to assess whether environmental conditions experienced during the 2019–2020 mega‐fire season were anomalous. Location South‐eastern Australia. Time period 1953–2020. Major taxa studied Temperate forests. Methods We used satellite‐derived fire severity mapping from 1988 to 2020 to model the effects of drought, weather and fuels on the annual area burned and the proportion of the area burned that was impacted by high‐severity fire across four bioregions. Trends in wildfire extent and severity were then estimated from 1953 to 2020 using these derived models and gridded climate data to assess changes in climatic potential for large and severe wildfires. Estimates of wildfire extent and severity for the 2019–2020 fire season were then assessed against prior seasons (1953–2019). Results Annual area burned was positively related to the severity of seasonal drought and frequency of fire weather conditions that promote substantial daily fire growth. Wildfire severity was elevated in years with severe fire weather and increased with increasing antecedent drought in years without severe fire weather. Fuels had a lesser effect on wildfire extent and severity than climate. Potential fire extent and severity have increased over time in response to an increased severity of drought and worsening fire weather conditions. Estimates of wildfire extent and severity during the 2019–2020 fire season approached the upper extreme within each bioregion, owing to widespread extreme climatic conditions. Main conclusions The climatic potential for large and severe forest fires has increased across south‐eastern Australia since the 1950s, probably because of anthropogenic climate change. The magnitude and severity of the 2019–2020 fires reflected climatic conditions that are driving an increase in the size and severity of wildfires.

The carbon cost of the 2019–20 Australian fires varies with fire severity and forest type - Rachael H. Nolan; Luke Collins; Rebecca K. Gibson; Stephanie A. Samson; Katherine T. Rolls; Kirsty Milner; Belinda E. Medlyn; Owen F. Price; Anne Griebel; Brendan Choat; Mingkai Jiang; Matthias M. Boer (Global Ecology and Biogeography, 2022)
Aim To estimate loss of above‐ground carbon (AGC) and conversion of live carbon to dead carbon following understorey and canopy fire. Location South‐eastern Australia. Time period 2019–2020. Major taxa studied Four widespread resprouting eucalypt forests. Methods Above‐ground carbon was measured in 15 plots in each of four forest types one‐year post‐fire. We also assessed topkill, that is, trees subject to canopy loss that failed to resprout epicormically. Results While canopy fire was associated with greater declines in AGC than understorey fire, this was only statistically significant for only one forest type, where AGC declined from 154 to 85 Mg C ha −1 following canopy fire. Significant post‐fire increases in dead AGC were observed in one forest type, where dead carbon increased from 22 to 60% after canopy fire. Topkill of trees following canopy fire (48–78% of stems) was higher than topkill after understorey fire (36–53% of stems) and in unburnt forest (12–55%). Topkill occurred primarily in small‐diameter stems. Consequently, there was no effect of fire on the proportion of dead AGC in trees, with the exception of the forest with lowest productivity (i.e., lowest biomass) and lowest annual rainfall, where dead tree carbon increased from 8% in unburnt forest to 13 and 53% after understorey and canopy fire, respectively. AGC in understorey vegetation and coarse woody debris was similar or lower in burnt compared with unburnt forest. Litter carbon was significantly lower and pyrogenic carbon significantly higher in burnt forest, with no difference between understorey and canopy fire. Main conclusions While increased fire severity was associated with increased changes to carbon stocks, there were differences among forest types. Specifically, the driest forest type had the highest rates of topkill following canopy fire. These results highlight the importance of spatial variability in fire severity and forest type in determining the effects of fire on carbon stocks.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Three Glycotypes in the London Classification System of Sporadic Creutzfeldt-Jakob Disease Differ in Disease Duration - Blair Ney; Dhamidhu Eratne; Victoria Lewis; Luke Ney; Qiao-Xin Li; Christiane Stehmann; Steven Collins; Dennis Velakoulis (Molecular Neurobiology, 2021)

The Role of the Dental Community in Oropharyngeal Cancer Prevention Through HPV Vaccine Advocacy - Thomas Luke Arnell; Collin York; Alexis Nadeau; Maeve Lauren Donnelly; Laura Till; Pedram Zargari; Wendy Davis; Christine Finley; Thomas Delaney; Jan Carney (Journal of Cancer Education, 2021)

A broader perspective on the causes and consequences of eastern Australia's 2019–20 season of mega‐fires: A response to Adams et al. - Ross A. Bradstock; Rachael H. Nolan; Luke Collins; Víctor Resco de Dios; Hamish Clarke; Meaghan Jenkins; Belinda Kenny; Matthias M. Boer (Global Change Biology, 2020)
This article is a Response to Adams et al . 26, 3756–3758 . See also the Letter by Nolan et al . 26, 1039–1041 .

Causes and consequences of eastern Australia's 2019–20 season of mega‐fires - Rachael H. Nolan; Matthias M. Boer; Luke Collins; Víctor Resco de Dios; Hamish Clarke; Meaghan Jenkins; Belinda Kenny; Ross A. Bradstock (Global Change Biology, 2020)
See Letter to the Editor on this article by Adam et al ., 26, 3756–3758 . See also Response to the Letter by Bradstock et al ., 26, e8–e9 .

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Wildfire refugia in forests: Severe fire weather and drought mute the influence of topography and fuel age - Luke Collins; Andrew F. Bennett; Steve W. J. Leonard; Trent D. Penman (Global Change Biology, 2019)
Wildfire refugia (unburnt patches within large wildfires) are important for the persistence of fire‐sensitive species across forested landscapes globally. A key challenge is to identify the factors that determine the distribution of fire refugia across space and time. In particular, determining the relative influence of climatic and landscape factors is important in order to understand likely changes in the distribution of wildfire refugia under future climates. Here, we examine the relative effect of weather (i.e. fire weather, drought severity) and landscape features (i.e. topography, fuel age, vegetation type) on the occurrence of fire refugia across 26 large wildfires in south‐eastern Australia. Fire weather and drought severity were the primary drivers of the occurrence of fire refugia, moderating the effect of landscape attributes. Unburnt patches rarely occurred under ‘severe’ fire weather, irrespective of drought severity, topography, fuels or vegetation community. The influence of drought severity and landscape factors played out most strongly under ‘moderate’ fire weather. In mesic forests, fire refugia were linked to variables that affect fuel moisture, whereby the occurrence of unburnt patches decreased with increasing drought conditions and were associated with more mesic topographic locations (i.e. gullies, pole‐facing aspects) and vegetation communities (i.e. closed‐forest). In dry forest, the occurrence of refugia was responsive to fuel age, being associated with recently burnt areas (

Aboveground carbon sequestration in dry temperate forests varies with climate not fire regime - Christopher E. Gordon; Eli R. Bendall; Mitchell G. Stares; Luke Collins; Ross A. Bradstock (Global Change Biology, 2018)
The storage of carbon in plant tissues and debris has been proposed as a method to offset anthropogenic increases in atmospheric [ CO 2 ]. Temperate forests represent significant above‐ground carbon ( AGC ) “sinks” because their relatively fast growth and slow decay rates optimise carbon assimilation. Fire is a common disturbance event in temperate forests globally that should strongly influence AGC because: discrete fires consume above‐ground biomass releasing carbon to the atmosphere, and the long‐term application of different fire‐regimes select for specific plant communities that sequester carbon at different rates. We investigated the latter process by quantifying AGC storage at 104 sites in the Sydney Basin Bioregion, Australia, relative to differences in components of the fire regime: frequency, severity and interfire interval. To predict the potential impacts of future climate change on fire/ AGC interactions, we stratified our field sites across gradients of mean annual temperature and precipitation and quantified within‐ and between‐factor interactions between the fire and climate variables. In agreement with previous studies, large trees were the primary AGC sink, accounting for ~70% of carbon at sites. Generalised additive models showed that mean annual temperature was the strongest predictor of AGC storage, with a 54% near‐linear decrease predicted across the 6.1°C temperature range experienced at sites. Mean annual precipitation, fire frequency, fire severity and interfire interval were consistently poor predictors of total above‐ground storage, although there were some significant relationships with component stocks. Our results show resilience of AGC to frequent and severe wildfire and suggest temperature mediated decreases in forest carbon storage under future climate change predictions.

Understorey productivity in temperate grassy woodland responds to soil water availability but not to elevated [CO 2 ] - Luke Collins; Ross A. Bradstock; Victor Resco de Dios; Remko A. Duursma; Sabrina Velasco; Matthias M. Boer (Global Change Biology, 2018)
Rising atmospheric [CO 2 ] and associated climate change are expected to modify primary productivity across a range of ecosystems globally. Increasing aridity is predicted to reduce grassland productivity, although rising [CO 2 ] and associated increases in plant water use efficiency may partially offset the effect of drying on growth. Difficulties arise in predicting the direction and magnitude of future changes in ecosystem productivity, due to limited field experimentation investigating climate and CO 2 interactions. We use repeat near‐surface digital photography to quantify the effects of water availability and experimentally manipulated elevated [CO 2 ] (eCO 2 ) on understorey live foliage cover and biomass over three growing seasons in a temperate grassy woodland in south‐eastern Australia. We hypothesised that (i) understorey herbaceous productivity is dependent upon soil water availability, and (ii) that eCO 2 will increase productivity, with greatest stimulation occurring under conditions of low water availability. Soil volumetric water content (VWC) determined foliage cover and growth rates over the length of the growing season (August to March), with low VWC ( 3 m −3 ) reducing productivity. However, eCO 2 did not increase herbaceous cover and biomass over the duration of the experiment, or mitigate the effects of low water availability on understorey growth rates and cover. Our findings suggest that projected increases in aridity in temperate woodlands are likely to lead to reduced understorey productivity, with little scope for eCO 2 to offset these changes.

Vertical (arboreality) and horizontal (dispersal) movement increase the resilience of vertebrates to climatic instability - Brett. R. Scheffers; Luke Shoo; Ben Phillips; Stewart L. Macdonald; Alex Anderson; Jeremy VanDerWal; Collin Storlie; Arnaud Gourret; Stephen E. Williams (Global Ecology and Biogeography, 2017)
Aim Species that respond favourably to environmental change tend to be mobile or dispersive. Living within trees has some benefits over life on the ground. Species that move vertically within forest canopies can take advantage of increased complexity and resource availability, which should correspond to increased resilience to environmental variability and change. Here we show that two modes of movement, arboreality and horizontal dispersal, across an entire bioregional vertebrate fauna in the rain forests of Australia are associated with measures of historical environmental stability. Location Wet Tropics, Queensland, Australia. Time period Historical (c. 20,000 years ago) and current (1990‐2009). Major taxa studied Mammal, bird, reptile, and frog species. Methods We analysed vertebrate distribution for 195 species and trait data from 20 years of standardized sampling. We derived an arboreality index (i.e., the extent of vertical habitat used by each species) from a large database of field observations combined with expert opinion scores on arboreality. We compared community‐wide trends in arboreality and their horizontal dispersal potential with historical climate since the Last Glacial Maximum ( c . 20,000 years ago) and current climate over 20 years of the recent past (1990–2009). Results Vertical (arboreality) and horizontal (dispersal) movement were positively correlated, and both were negatively correlated with environmental stability. We found that arboreal species dominate communities in historically unstable areas, and these areas have both low richness and low endemism. Further, we show that low‐ and high‐altitude arboreal species experience similar thermal regimes, whereas low‐ and high‐altitude ground‐dwelling species experience little overlap in thermal regimes. Main conclusion Higher variability and overlap in temperature among rain forest canopies suggests less geographical separation in tolerable conditions for arboreal taxa when compared with ground‐dwelling taxa. Increased ecological plasticity in horizontal and vertical movement as well as exposure and pre‐selection to high temperature variability appears to allow arboreal species to exploit climatically uncertain areas, a capacity that may serve them well in responding to future climate change.

Efficacy of chlorine, chlorine dioxide and ultraviolet radiation as disinfectants against plant pathogens in irrigation water - Kelly Scarlett; Damian Collins; Len Tesoriero; Luke Jewell; Floris van Ogtrop; Rosalie Daniel (European Journal of Plant Pathology, 2016)

Erratum to: The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

Potential for mountaintop boulder fields to buffer species against extreme heat stress under climate change - Luke P. Shoo; Collin Storlie; Yvette M. Williams; Stephen E. Williams (International Journal of Biometeorology, 2010)